A companion to the Reconstruction Presidents, 1865-1881 - Frantz, Edward O. (Chichester, West Sussex : Wiley-Blackwell, 2014)
A Companion to Reconstruction Presidents presents a series of original essays that explore a variety of important issues, themes, and debates associated with the presidencies of Andrew Johnson, Ulysses S. Grant, and Rutherford B. Hayes. Represents the first comprehensive look at the presidencies of Johnson, Grant, and Hayes in one volumeFeatures contributions from top historians and presidential scholarsApproaches the study of these presidents from a historiographical perspectiveKey topics include each president's political career; foreign policy; domestic policy; military history; and social.
Front Matter -- Introduction -- Andrew Johnson. Andrew Johnson before the Presidency / Glenna R Schroeder-Lein -- Andrew Johnson and Reconstruction / Erik Mathisen -- Andrew Johnson / Aaron Astor -- The Impeachment of Andrew Johnson / Luis Fuentes-Rohwer -- Foreign Affairs and Andrew Johnson / Richard Zuczek -- Ulysses S. Grant / Pamela K Sanfilippo -- Ulysses S. Grant / Brian Steel Wills -- Ulysses S. Grant / Brian Holden Reid -- The General-in-Chief, 1864-1865 / William B Feis -- Ulysses S. Grant Goes to Washington / James J Broomall -- The 1868 and 1872 Elections / Andrew Prymak -- Looking for the Popular Culture of Grant's America / Woody Register -- Reconstruction during the Grant Years / Thomas R Pegram -- Flames in the West / Eric J Morser -- Avoiding War / Stephen McCullough -- Grant and Historical Memory / John F Marszalek -- Grant and Heroic Leadership / Frank J Williams -- Engagement Rather Than Escape / William M Ferraro -- Rutherford B. Hayes. Crushing the Traitors / John R Lundberg -- Rutherford B. Hayes / Allan Peskin -- Election of 1876/Compromise of 1877 / Marc-William Palen -- Hayes and Civil Service Reform / Ari Hoogenboom -- The Shattered Dream / Eric Leif Davin -- Lifting the Veil of Obscurity? / Katherine E Rohrer -- Edison and the Age of Invention / David Hochfelder -- Centennial Celebrations / John Hepp -- Community Responsibilities, Citizenship Rights / Michelle Kuhl -- Playing on a New Field / Roman J Hoyos -- Scandal, Corruption / Robert W Burg -- Ex-Presidents in the Age of Reconstruction / Edward O Frantz.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed on May 29, 2014).
Keywords: Reconstruction (U.S. history, 1865-1877); Presidents -- United States -- History -- 19th century; United States -- Politics and government -- 1865-1877.; Politics and government; Presidents; United States; 1800-1899; Electronic books; History